Evaluating the Antioxidant and Xanthine Oxidase Enzyme Inhibitory Activities in vitro of Piper betle Linn. Leaf Extract - Thanh Tung, Bui; Ky Duyen, Duong Thi; Nhat, Bui Son (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 2DO - 10.25073/2588-1132/vnumps.4231, 2020)
In this study, leaves of Piper betle L. were extracted by ultrasonic with ethanol 50% and successively fractionated with n-hexane, ethyl acetate (EtOAc) and n-butanol (n-BuOH) solvents. These fractions were evaluated for their antioxidant and xanthine oxidase inhibitory activities in vitro . The study results show that EtOAc fraction had the highest antioxidant effect (IC 50 : 15.54 ± 0.48 µg/mL), followed by EtOH fraction (IC 50 : 31.31 ± 0.12 µg/mL), n-hexane fraction (IC 50 : 83.67 ± 0.14 µg/mL), and the lowest was n-BuOH fraction (IC 50 : 95.60 ± 0.37 µg/mL). The evaluation of XO enzyme inhibition shows that EtOAc fraction extract had the strongest XO enzyme inhibitory activity (IC 50 : 29.65 ± 0.93 µg/mL), followed by n-BuOH fraction (IC 50 : 37.22 ± 1.23 µg/mL), EtOH fraction (IC 50 : 52.13 ± 0.56 µg/mL), and the lowest was n-hexane fraction (IC 50 : 80.12 ± 0.21 µg/mL). These results indicate that the EtOAc fraction from the leaf of Piper betle L. can be used for the prevention and treatment of gout. Keywords Gout, Piper betle Linn., xanthine oxidase, antioxidant activity References [1] Y. Niu, W. Lu, L. Gao, H. Lin, X. Liu, L. Li. Reducing effect of mangiferin on serum uric acid levels in mice. Pharmaceutical Biology 50(9) (2012) 1177. [2] M. Zarepour, K. Kaspari, S. Stagge S, R. Rethmeier, R.R, Mendel, F. Bittner. Xanthine dehydrogenase AtXDH1 from Arabidopsis thaliana is a potent producer of superoxide anions via its NADH oxidase activity. Plant Molecular Biology 72 (2010) 301. [3] Cotelle N. Role of Flavonoids in Oxidative Stress. Current Topics in Medicinal Chemistry 1(6) (2001) 569. [4] S. Das, R. Parida, I.S. Sandeep, S. Nayak, Mohanty, S. Biotechnological intervention in betelvine (Piper betle L.): A review on recent advances and future prospects. Asian Pacific Journal of Tropical Medicine 9(10) (2016) 938. [5] V. Dwivedi, S. Tripathi. Review study on potential activity of Piper betle. Journal of Pharmacognosy and Phytochemistry 3(4) (2014) 93. [6] H.P. Baviskar, G.T. Dhake, M.A. Kasai, N.B. Chaudhari, T.A. Deshmukh. Review of Piper Betle. Research Journal of Phamacognosy and Phytochemischy 9(2) (2017). [7] C. Risdian, W. Widowati, T. Mozef, T.L. Wargasetia, K. Khiong. Free Radical Scavenging Activity of Ethanolic Leaves Extract and Its Different Solvent Fractions of Piper betle L. In Vitro. Indonesian Journal of Cancer Chemoprevention 2(1) (2011) 141. [8] D. Rintu, M. Shinjini, M. Kaustab, P. Pramathadhip, P.S. Umesh, E.R. Banerjee. Anti-Oxidant and Anti-Inflammatory Activities of Different Varieties of Piper Leaf Extracts (Piper Betle L.). Journal of Nutrition & Food Sciences 5(5) (2015). [9] K.Y. Pin, A. L. Chuah, A. A. Rashih, M.P. Mazura, J. Fadzureena, S. Vimala, M.A. Rasadah. Antioxidant and anti-inflammatory activities of extracts of betel leaves (Piper betle) from solvents with different polarities. Journal of Tropical Forest Science 22(4) (2010) 448. [10] T. Noro et al, Inhibitors of xanthine oxidase from the flowers and buds of Daphne genkwa. Chemical and Pharmaceutical Bulletin 31(11) (1983) 3984. [11] M. Umamaheswari, K. AsokKumar, A. Somasundaram, T. Sivashanmugam, V. Subhadradevi, T.K. Ravi. Xanthine oxidase inhibitory activity of some Indian medical plants. Journal of Ethnopharmacology 109(3) (2007) 547. [12] D.E. Van Hoorn, et al, Accurate prediction of xanthine oxidase inhibition based on the structure of flavonoids European journal of pharmacology 451(2) (2002) 111. [13] N. Cotelle, Role of flavonoids in oxidative stress. Current topics in medicinal chemistry 1(6) (2001) 569. [14] J.M. McCord. Oxygen-derived free radicals in postischemic tissue injury. New England Journal of Medicine 312(3) (1985) 159. [15] P.V. Chakravarthi, S. Murugesan, A. Arivuchelvan, K. Sukumar, A. Arulmozhi, A. Jagadeeswaran. In vitro xanthine oxidase inhibitory activity of Piper betle and Phyllanthus niruri. Journal of Pharmacognosy and Phytochemistry 7(5) (2018) 959.